Integration of History Learning and Digital Tourism: Utilizing AI for Cultural Conservation in the Ijen Geopark Region for Senior Secondary Students in Banyuwangi - Widyasari, Riztika; Santi, Triana Kartika; Mahfud; Wisnu (International Journal of Learning Reformation in Elementary Education, 2025)
Ijen Geopark has been designated a priority area in the UNESCO Global Geopark network since 2023 due to its rich geological, biological, and cultural diversity. However, this potential has not been fully utilized in local history education at the high school level. This study aims to develop a history learning module based on digital tourism and artificial intelligence (AI) for cultural conservation among high school students in Banyuwangi. This study adopted a Research and Development model that includes needs analysis, product design, limited trials, revisions, and implementation evaluation. The sample consisted of 190 students, 8 history teachers, and 18 schools. Data analysis used paired sample t-tests, Pearson correlation, and one-way ANOVA. The results showed an increase in knowledge scores from 52.1 to 80.3 and conservation attitudes from 3.1 to 4.2. The correlation between digital media use and learning outcomes yielded r = 0.62. Teachers rated the module's feasibility with an average of 4.3. It was concluded that this learning medium was effective in improving historical understanding and cultural awareness. Recommendations include improving internet infrastructure, providing teacher training, and implementing long-term, community-based evaluations. This study proposes a relevant, innovative, and contextual model for history education in the digital age.